Critical aspects of impedance spectroscopy in silicon solar cell characterization: A review. (September 2017) - Yadav, Pankaj; Pandey, Kavita; Bhatt, Vishwa; Kumar, Manoj; Kim, Joondong
Abstract: Solar energy generation and utilization is dominated by silicon based solar photovoltaic technology, which has a market share of 80–90% of the solar photovoltaic industry worldwide. The performance indicating parameters of silicon solar cells include power conversion efficiency, series and shunt resistance, ideality factor and built-in potential. These parameters are mostly characterized by DC techniques, which is limited by its insufficiency to identify other important parameters such as interfacial diffusion and transition capacitance and resistive and capacitive components of p-p + interface of a silicon solar cell. Impedance spectroscopy is considered to be one of the most promising techniques for the characterization of abovementioned performance limiting parameters of a solar cell. In order to address the decoupling of various physical processes associated with different interfaces of a solar cell, quantitative analysis of the impedance spectroscopic data is required. An appropriate mathematical model is frequently used to correlate with the physical performance limiting parameters. This review presents a complete overview of the required mathematical models to analyse impedance spectroscopic data for interfacial processes of silicon solar cell.